BUSINESS LAW AND ETHICS IN INDONESIA : THE IMPACT OF ECONOMIC PRACTICES ON NATURAL RESOURCES - Kurniawan, Wahyu (Communale Journal, 2025)
This article examines the complex relationship between morality and business ethics in the context of Indonesian law. Taking a normative approach and using conceptual and comparative research methods, this study explores the impact of business law on ethical practices that are increasingly important amid rapid economic growth and intense business competition. An understanding of business ethics is closely related to moral conduct in business activities, which is important for maintaining corporate reputation and consumer trust. In addition, this article explores the challenges faced by companies in implementing effective ethical and legal practices, as well as the negative impacts of unethical business practices, such as environmental damage and human rights violations. This research underscores the importance of integrating ethics in business strategy to support sustainable economic growth and societal well-being.